Retaining and motivating knowledge-workers in a time of crisis - the case of the management consultancy market - Fodor, Péter; Weiner, János (Marketing & Menedzsment, 2019)
Management consultancy (MC) was one of the fastest growing businesses of the last decade and still has a stronger-than-average potential for growth than the traditional sectors. However, in this period of global economic crisis, growth is no longer assured and the usual management consulting firm model simply does not work in every situation. Current economic circumstances pose new challenges for this market. In this paper the European management consultancy market is introduced with a focus on problems most of the knowledge-based companies meet and after a dicussion of symptoms of the problems it concludes to practices applicable not only to consultancy businesses, but, generally, to companies dependent upon knowledge-workers.